Media Pembelajaran Berbasis Web Untuk Siswa SMK Jurusan RPL Pada Mata Pelajaran Pemrograman Web Dasar - Mardani, Alvian Dwi; , Prof. Dr. Budi Murtiyasa, M.Kom (2017)
Basic web programming is one of the subjects that are important in the Software Engineering Departement. Basic web programming is regarded as one of the subjects that are difficult to learn especially for those who are new to learn about web programming. Negative perceived about basic web programming subjects affected by inaccurate selection of learning media. It can affect student interest in learning basic web programming. On this basis is necessary to develop an interactive learning media that can enhance student interest. Web-based learning media is one alternative in learning activities. In order to improve the quality of education needed innovative learning process so as to enable the learning process can be done anytime and anywhere as long as connected to the Internet. Teaching and learning activities using the textbook as a media that has been applied in vocational schools can be addressed by providing interactive learning facility. This research was conducted to develop a system that can be used as an alternative of learning media to replace the printed book with a web-based system on the basic web programming subject for vocational students in Software Engineering Major. The results of the research in the form of a web-based learning media can assist students in acquiring the material. In addition, students can also do the exercises provided by the teacher as a benchmark of basic knowledge of web programming.